2010
DOI: 10.1002/jcb.22739
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic intermittent hypoxia on biological behavior and hypoxia‐associated gene expression in lung cancer cells

Abstract: Hypoxia plays an important role in the development of solid tumors and is associated with their therapeutic resistance. There exist three major forms of hypoxia: acute, chronic, and intermittent hypoxia. Previous studies have shown that cancer cells could behave in the form of adaptation to hypoxia in tumor growth, which could result in their biological changes and determine their responses to the therapies. To investigate the tumor cells' adaptation to hypoxia, we recreated two models using two lung cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 30 publications
1
38
2
2
Order By: Relevance
“…While previous findings have shown that IH promotes cancer cell proliferation, as demonstrated by cell growth assays and cell cycle analysis [26], we did not observe any significant difference in biological behavior such as cell cycle progression or proliferation of melanoma cells that were maintained under normoxia or pre-IH-conditioned. These discrepancies might be due to , and GLUT1 mRNA-expression levels in tumors from mice in the N, IH-1, and IH-2 groups.…”
Section: Discussioncontrasting
confidence: 99%
“…While previous findings have shown that IH promotes cancer cell proliferation, as demonstrated by cell growth assays and cell cycle analysis [26], we did not observe any significant difference in biological behavior such as cell cycle progression or proliferation of melanoma cells that were maintained under normoxia or pre-IH-conditioned. These discrepancies might be due to , and GLUT1 mRNA-expression levels in tumors from mice in the N, IH-1, and IH-2 groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Liu and colleagues demonstrated that intermittent hypoxia treated H446 lung cancer cells had a greater metastatic ability and radio-resistance. They found HIF-1α was involved in both processes [84]. Intermittent hypoxia exposed endothelial cells also showed enhanced migration and exhibited an increased resistance against irradiation as compared to their counterparts grown in normoxia or acute hypoxia.…”
Section: Expression Of the Hif-1 System Under Intermittent Hypoxiamentioning
confidence: 98%
“…In a separate study, intermittent hypoxia treated A549 and H446 lung cancer cells exhibited increased invasion in comparison to normoxic cells. Down-regulation of the HIF-1α gene decreased the cellular migration in these cells, thereby linking HIF-1 to cancer cell invasion under intermittent hypoxia [84]. Moreover, both thioredoxin and HIF-1 have been linked to the development of resistance against anticancer therapeutics [82,96,97].…”
Section: The Interaction Of Redox and Hypoxic Pathways Under Intermitmentioning
confidence: 99%
“…32 In our subgroup analyses, similar to the study by Campos-Rodriguez and colleagues, 3 we found that oxygen desaturation, but not the apneahypopnea index, was significantly associated with smoking-related cancers. Hypoxia has been shown to cause upregulation and over expression of a number of genes related to biological behaviours of cancer cells, including apoptosis, metastasis and angiogenesis, 33 which renders the cancer cells more aggressive and resistant to therapy. 34 Indeed, chronic intermittent hypoxia has been shown to accelerate cancer progression in a mouse model of sleep apnea.…”
Section: Discussionmentioning
confidence: 99%